Domain Rezeki pada Peribahasa Indonesia dalam Kajian Semantik Inkuisitif - S.J, Syahidah Azimi; Lestari, Finie; Yeniza, Ilma Putri; Hermandra, Hermandra (Prodi Perpustakaan dan Sains Informasi, 2023)
The review that has been reviewed from the inquisitive semantic study here is not yet perfect in finding the true meaning of this study in Indonesia. However, after being observed and studied in various studies regarding inquisitive semantics, this study is a material concept that wants to be expressed by conveying more in-depth material about an essence or appropriate part of the study in a proverb in inquisitive semantics. The aspect of teaching proverbs is considered useful for the country, various concepts of proverb study are inherent in every delivery in the presentation process anywhere and at any time. This study in proverbs really produces a symbol and policy from the Malay people. Of course, the decline caused by the educational system has resulted in actions and manners being conveyed in depth because they are fully explored. Fortune is a person's intention or self who wants in his heart to give a sense of blessing to two people who give a sense of love to each other. Or the blessings that have been given by God with all the prayers that we have dreamed of with requests to God in the form of life in this world. Here it can be seen that the explanation regarding the word sustenance from the previous explanation regarding the views of the country in Indonesia is involved and has a proverbial saying. The publisher or author of the proverb here is a current Indonesian ancestor who has studied the use of this proverb by using it as a word of advice and so on. By searching and finding, steps are taken such as presenting the material, concluding the differences from semantics.